Stealing history: art theft, looting, and other crimes against our cultural heritage - Clarke, Colleen Margaret (Rowman & Littlefield, 2017)
Medias portrayal of art crime -- Why does art matter? -- What is art crime? -- History of art, and art related crimes -- Cultural differences between United States and Europe, and how it affects art crime -- Looting of art and archeological sites -- Economic impact of art and art related crimes -- Museums : our identity and culture -- Police demands, scrutiny, education, and the future -- Ways in which law enforcement can focus on art crimes -- Security & policing in art crime throughout the world -- Growth of art crime, and art crime prevention